If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 1 = -29 Reorder the terms: 1 + -6x = -29 Solving 1 + -6x = -29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6x = -29 + -1 Combine like terms: 1 + -1 = 0 0 + -6x = -29 + -1 -6x = -29 + -1 Combine like terms: -29 + -1 = -30 -6x = -30 Divide each side by '-6'. x = 5 Simplifying x = 5
| 2.25r+4=21.50 | | 2x+3=-9-x | | 27C^2+39cd+14d^2=0 | | 5+4x=-39 | | a^2-17ab+72b^2=0 | | (2w+7)w-99=0 | | 10+2x=26 | | 3(x-8)=4(3x+2)-5 | | 6(3x-5)-7x=22 | | 8x^3+28x^2+20x=0 | | 1+(-a/9)-4=0 | | 0.4x+0.2=-1 | | x^10=30 | | y=-3(1)+5 | | .25(8y-4)=x | | 7(x-2)=7x-14 | | a^4-a^2-6=0 | | 7x-(5x-2)=-8 | | -25n^2+57n=-14 | | 6x+8.74=4x+11 | | (2w+5)w-42=0 | | 18=-32w+20 | | y=-3(0)+5 | | 5,-2= | | 2-y=5wz+15 | | 8-m+3m=16 | | 7(x+2)=-56 | | -0.9p+-3=0.6 | | -3-7x=-24 | | -3x+2=7x-8 | | (5,-2)m= | | 4x^2+7x-10=0 |